Institutional Aspects of the Withdrawal Process from the European Union -Brexit and Post-Brexit - Tanja Miščević; Nemanja Purić (Međunarodni Problemi, 2024)
Interdependence in a globalized world implies managing processes in many areas that are regulated at the international level – this is the role that International Governmental Organizations have adopted during the century of their existence. Their work and success are causally linked to the competencies and decision-making processes, as well as to the breadth and agility of member states. This is the reason why many International Organizations do not provide options for withdrawal or exclusion from membership. In that regard, European Union, as a supranational international organization, is proving its uniqueness in the international organizing. Considering that the Lisbon Treaty envisaged for the first time institute of withdrawal in Article 50, this possibility has been the subject of numerous theoretical debates, but it also become practice. The UK’s withdrawal agreement from the EU marked the beginning of new type of negotiations as well as the future relations between former Member State and the European Union. The paper analyzes three institutional aspects of the withdrawal process. Firstly, the procedure envisaged in Article 50 of the Treaty which is, in comparison to typical international organizations, more institutionalized. Secondly, the withdrawal negotiations concluded with the signing of the Trade and Cooperation Agreement that set standards for potential future withdrawals, and this paper examines its institutional aspects focusing on dispute resolution. Thirdly, the paper analyzes the institutional aspects of the Trade and Cooperation Agreement, which establishes a new form of association as a legal framework for the future relations between the withdrawing state and the European Union. The authors use a comparative method to determine the institutional peculiarities of the agreements.